Emerging communication technologies and the society - Balakrishnan, N.; Indian National Science Academy; Seminar on "Emerging Communication Technologies and the Society" (1999 : Indian National Science Academy) (New Delhi : Narosa Pub. House, 2000)
Proceedings of the Seminar on "Emerging Communication Technologies and the Society", held on 15-16 March, 1999, at Indian National Science Academy, New Delhi.
"Indian National Science Academy, New Delhi."
Includes bibliographical references.
Keywords: Information technology -- Social aspects -- India -- Congresses